Respuesta :
Answer:
x-2 is a factor of p(x)
Step-by-step explanation:
To calculate whether x-2 is a factor of p(x), you have to substitute x = 2 into the function :
p(x) = x⁴ - 3x² + 2x - 8
Let x = 2,
p(2) = 2⁴ - 3(2)² + 2(2) - 8
= 16 - 12 + 4 - 8
= 0
*If p(x) is 0, means that it is the correct factor. If
p(x) is not equals to 0, it is not a factor of p(x).
Answer:
It is a factor
Step-by-step explanation:
If x - 2 is a factor, x = 2 should be a root
p(2) = 2⁴ - 3(2²) + 2(2) - 8
p(2) = 0
Therefore 2 is a root and x - 2 is a factor